Role of the pair correlation function in the dynamical transition predicted by mode coupling theory - Nandi, Manoj Kumar; Banerjee, Atreyee; Dasgupta, Chandan; Bhattacharyya, Sarika Maitra (Physical Review Letters, 2017)
In a recent study, we have found that for a large number of systems the configurational entropy at the pair level S-c2, which is primarily determined by the pair correlation function, vanishes at the dynamical transition temperature T-c. Thus, it appears that the information of the transition temperature is embedded in the structure of the liquid. In order to investigate this, we describe the dynamics of the system at the mean field level and, using the concepts of the dynamical density functional theory, show that the dynamical transition temperature depends only on the pair correlation function. Thus, this theory is similar in spirit to the microscopic mode coupling theory (MCT). However, unlike microscopic MCT, which predicts a very high transition temperature, the present theory predicts a transition temperature that is similar to T-c. This implies that the information of the dynamical transition temperature is embedded in the pair correlation function.